Technology-assisted coaching can increase engagement with learning technology at home and caregivers' awareness of it. (October 2022) - Nazare, Juliana; Woolf, Anneli; Sysoev, Ivan; Ballinger, Sarah; Saveski, Martin; Walker, Marianna; Roy, Deb
Abstract: While digital technologies are typically used to support established educational roles, they can also enable new roles, providing guidance for learners at previously inaccessible points in the learning process (e.g., at home, on-the-go). This work presents one such role — a technology-assisted human coach — that relies on digital technology to offer a personally-tailored learning experience where children can engage in self-motivated, personally meaningful exploration at home using mobile literacy apps and coaches can scaffold children's learning asynchronously based on their play data. To investigate the feasibility and effectiveness of this virtual coaching role, we created two instantiations of a coaching system using open-ended literacy apps. We conducted a randomized controlled trial and a formative study. We found that it is feasible for a novel computer system to assist a human coach in analyzing and supporting children's learning and discussing progress with caregivers to help them co-engage. Our analysis shows that coaches successfully fulfilled their role as designed, and that the coaching system was effective in increasing caregivers' awareness of their children's in-app play and playtime with the literacy app, but not in increasing the variety of words children made. Furthermore, we found that for families with lower formal education levels, the effects of the coaching system were significantly stronger across almost all outcomes investigated. Considering these findings, we contribute guidance on how to create new roles in children's learning enabled by data-driven systems that can reach learners at a traditionally difficult-to-access part of the learning process and support self-motivated learning. Graphical abstract: Image 1 Highlights: We present a technology-assisted coaching role to support children's learning. We built a digital system to enable coaching children remotely using literacy apps. We ran a pilot and RCT to study the coaching system's feasibility and effectiveness. System increased caregiver awareness of child in-app play and child app playtime. Families with less formal education benefited more from the coaching system.